THE IMPACT OF INDEPENDENCY OF COMMISSARY, INSTITUTIONAL OWNERSHIP, AND UNDERWRITER REPUTATION TOWARDS IPO UNDERPRICING COMPANIES LISTED IN INDONESIAN STOCK EXCHANGE 2011-2015 - Rasimin, Octaviany B1024131013 (Jurnal Manajemen Update, 2017)
IPO (Initial Public Offering) is an alternative for the private company to develop and increase the company?s capital with the help of public or potential investors to meet its financing needs but, most of the company which undergoing the IPO faced underpricing. Although, there are a lot of underpricing research has been conducted, but most of the studies focused on financial information. In this study, the samples of the study will exclude the financial companies such as banking industry and use corporate governance variable such as independency of commissary, institutional ownership, and underwriter reputation with period of study 2011-2015 which experienced underpricing on their IPO. The variables used in this study are underpricing as dependent variable, meanwhile, the independent variables used in this study the Independency of Commissioners,Institutional Ownership and Underwriter Reputation. The analytical method used to test the hypothesis in this study is Ordinary Least Squares regression (OLS). Finally, the study finds that Independency of board commissioners does not have significant relationship. Meanwhile, institutional ownership and underwriter reputation have significant relationship towards underpricing.Keywords: Initial Public Offering, IPO, Underpricing, Independency of board commissary, Ownership structure, Underwriter Reputation.